A Batching Approach to Quantile Estimation in Regenerative Simulations - Seila, Andrew F. (Management Science, 1982)
This paper presents a new method, called the batch quantile method, for estimating quantiles in regenerative simulations. The quantile estimator is consistent and asymptotically normal, and the method can be easily implemented and does not require prior knowledge of the range of values the data will assume. Empirical studies show adequate coverage of confidence intervals when batches of 50 cycles or more are used.